Enhancing the Therapeutic Potential of Purslane Leaf Extract (Portulaca oleracea) for Cholesterol Management - Juliana Christyaningsih; Fahin Izza; Regina Raiza; Azfa Alifatun Nayla; Deswita Aulia Pristanti; Faradyna Putri Az-Zahra; Mohd Nazil Salleh (International Journal of Advanced Health Science and Technology, 2024)
Cholesterol is one of the essential molecules in humans. An imbalance in cholesterol levels in the body, such as high levels of triglycerides and low-density lipoprotein (LDL) or total cholesterol, can contribute to one of the leading causes of death in Indonesia. Diseases caused by high cholesterol levels include cardiovascular diseases, atherosclerosis, hypercholesterolemia, hyperlipidemia, coronary heart disease, hypertension, and stroke [6,9,14]. As a result, additional intake from sources like omega-3-rich supplements or herbal remedies is recommended. Historically, plant-based treatments have been used as pharmacological therapies. Researchers have explored the use of purslane (Portulaca oleracea) leaves, which contain unsaturated fatty acids and antioxidants, including omega-3 fatty acids, vitamins A and C, and minerals such as magnesium and potassium, offering cardiovascular benefits. The researchers utilized purslane extract as an herbal tea blend, serving as a natural alternative to supplements in capsule form, which may be more expensive. In extract form, purslane leaves are hygienically processed and mixed with herbal tea, creating a convenient health drink for daily consumption. The purslane leaf extract was obtained through method maceration using 96% food-grade ethanol. Proximate tests were conducted to assess total energy, energy from fat, ash content, moisture content, carbohydrates (by difference), total fat, and protein content [5,24]. Sensory evaluation was conducted by semi-trained panelists to assess the color, aroma, and taste of herbal tea blends containing purslane leaf extract. This evaluation aimed to collect subjective feedback from potential consumers regarding the organoleptic characteristics of the product.